Abstract 256: Proposal of multimodal CT‐based scoring system in prediction of hemorrhagic transformation in acute ischemic stroke - Nada Elsaid (Stroke: Vascular and Interventional Neurology)
Introduction The routinely used computed tomography (CT)‐based workup in the setting of acute ischemic stroke (AIS) includes non‐contrast brain CT, CT angiography (CTA), and CT perfusion. Several CT, CTA, CTP‐based radiological biomarkers of hemorrhagic transformation (HT) were reported. To assess the predictive value of the combined multimodal CT parameters for HT after AIS and proposal of predictive scoring scale. Methods The source images of the NCCT, CTA and CTP of 282 AIS patients involving the anterior circulation (HT = 91, non‐HT = 191) were retrospectively reviewed and the following biomarkers were recorded and analyzed: Early subtle ischemic signs, hyperdense middle cerebral artery sign (HMCAS) and Alberta Stroke Program Early CT Score (ASPECTS) < 7 in NCCT, large‐vessel occlusion (LVO), clot burden score (CBS) < 6, large‐vessel occlusion, poor collateral score (CS) and Tmax > 6 s ≥ 56.5 ml. A scoring system to predict HT based on these biomarkers was developed. Each biomarker counts for a single point with the total score ranging from 0 to 7. Results All the aforementioned multimodal CT biomarkers and the selected cut offs were significantly associated with higher HT risk. The calculated scores were statistically significant different between the HT and the non‐HT groups with AUC 0.761 (95% CI 0.703–0.819, P < 0.0000001). Rates of HT were approximately five times higher in patients with score ≥ 3. Conclusion Multimodal CT‐based scoring system may provide highly reliable predictive model of hemorrhagic transformation in acute ischemic stroke.